NURSING CARE FOR PATIENTS DIAGNOSED WITH SYSTEMIC ARTERIAL HYPERTENSION:: INTEGRATIVE REVIEW - Rodrigues Feliciano, Lucyo (Health and Society, 2024)
Aging can bring about several diseases, including systemic arterial hypertension (SAH), which is why the present work has the general objective of demonstrating nursing care for patients diagnosed with systemic arterial hypertension. In relation to the specific objectives, it is: Identify the profile of the patient who presents systemic arterial hypertension; verify which activities are provided by nursing care with the aim of controlling hypertension; Analyze which means of care and prevention should be adopted to obtain a better quality of life in hypertensive patients. To this end, a literature review will be carried out, which is a review of the research of other authors on the aforementioned topic. Only from there will it be possible to catalog the intended results and obtain a more critical look at the relationship between SAH and aging.